2004
DOI: 10.1080/0261436042000251987
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood, stress and the exercise experience: freedom or constraint?

Abstract: Lack of leisure and time to self have been found to be major stressors for mothers. This paper examines perceived stress-relieving benefits gained from involvement in a 12 week exercise class program by a group of mothers (n = 30, x age = 37.3 years). Qualitative data indicated that exercise classes had the capacity to reduce perceived stress levels. The exercising mothers reported greater feelings of well-being mainly due to gaining a space of their own, time-out from busy schedules and the burden of childcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 21 publications
1
65
0
3
Order By: Relevance
“…The challenges posed by this phase of life include increased demands and responsibilities, 32,47 less discretionary time, 33 and internalized societal norms that dictate that women look after the needs of others before attending to their own. 48,49 The combination of these factors can lead to guilt when a woman's resources are spread thinly across various responsibilities. 47 It is not surprising, given these constraints, that women's self-care is likely to be impacted upon.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges posed by this phase of life include increased demands and responsibilities, 32,47 less discretionary time, 33 and internalized societal norms that dictate that women look after the needs of others before attending to their own. 48,49 The combination of these factors can lead to guilt when a woman's resources are spread thinly across various responsibilities. 47 It is not surprising, given these constraints, that women's self-care is likely to be impacted upon.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that LTPA enables women to experience feelings of happiness, fulfilment, embodied pleasure (Spowart, Burrows, & Shaw, 2010) along with feelings of strength and empowerment (Currie, 2004). While these subjective experiences are considered less measurable than standard health benefits and hence do not attract the same degree of import in the evidence-based discourses of public health, they are important to note.…”
Section: Ltpa and Resistancementioning
confidence: 98%
“…Whereas in the past a collective interpretation of women's experiences was predominant, there is an increasing realization that women are not an homogeneous group (Henderson & Allen, 1991) and that women have varying experiences of LTPA throughout their lives (e.g., Dionigi, 2002;Shaw, 1992). Although previous research (e.g., Currie, 2004) has provided evidence that women benefit from LTPA in a range of forms and are actively making space for LTPA in their lives, this is not necessarily the case for all women. Mothers with young children, in particular, still face a range of constraints to their participation in physical activity including fatigue, obligations to other roles, lack of time, and lack of social support and childcare (Bellow-Riecken & Rhodes, 2007;Mailey, Huberty, Dinkel, & McAuley, 2014;Miller & Brown, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Participants' time in this study went almost entirely towards exercising. Participants reported a strong appreciation for the convenience and flexibility of the intervention which are particularly important features for mothers of young children who report feeling overwhelmed and unable to prioritize their own self-care [15,[17][18][19]53]. Accordingly, our retention rates of 95% were higher than the two comparable technology trials on physical activity with mothers (86% and 75%), and among the highest of physical activity trials with mothers [14,[45][46][47][48][49]51,52].…”
Section: Feasibility and Acceptabilitymentioning
confidence: 64%
“…Active mothers have a positive influence on the activity levels of their children [11][12][13]. In addition, when mothers exercise, they report being able to manage better the demands of raising children [14][15][16][17]. Due to mothers' unique needs and risks, it is important that we design appropriate interventions to help mothers be more physically active.…”
Section: Introductionmentioning
confidence: 99%